Pemetaan Daerah Status Gizi Bermasalah Di Kabupaten Batang Berbasis Analisis Spasial - wahyu ningsih (Pena Medika Jurnal Kesehatan, 2019)
Continuous and comprehensive efforts need to resolve malnutrition problem in Indonesia. Riskesdas 2018, toddler nutrition problems were 17.7%, Severely underweight (3.9%) malnutrition (13.8%). Although it has significantly decreased, specific locus require more specific interventions such as resolve malnutrition,BGM, BBLR. In Batang (BGM) increased 806 cases in 2018. Malnutrition increased to 129 cases BBLR infants were still dominant at 601 case  in 2018. Purpose of research was to conduct mapping based on spatial analysis to determine areas that were prone to nutrition in Batang Regency. The method is secondary data processing from Dinas Kesehatan Kabupaten Batang in 2018 and then overlay with Quantum GIS software version 2.14.8. The result is an area with high malnutrition cases in Batang District at 36.08% including (Puskesmas Batang I, II, III and IV). Areas with high BGM toddlers cases in 2 districts namely Blado District by 12.16% (including Puskesmas Blado I, II) and Batang District by 16.50%. (including the areas of Batang I, II, III and IV). Areas that have a high BBLR predominance in Batang (Puskesmas Batang 1, Puskesmas Batang II and Puskesmas Batang IV) have BBLR cases of 20.13%. The highest problem-prone areas of nutrition are in Batang District which includes 4 working areas of Puskesmas, namely Batang 1, II and IV and some Puskesmas Batang III. Interventions carried out by: Optimizing Posyandu, Periodic Home Visit to families with nutritional problems. Synergy of the 4 pillars (health, agriculture, economy and education) hopes that they can complexly overcome nutritional problems as a whole